Sarmaci u wód. Podróż biskupa Józefa Sapiehy oraz Ignacego i Jana Łopacińskich do cieplic akwizgrańskich w 1740 r. - Kucharski, Adam (Klio - Czasopismo Poświęcone Dziejom Polski i Powszechnym, 2013)
In the 17th century resort departures became a constant element of landscape of polish abroad journeys. Such trend was an expression of wider interest for spa travel in Europe since the 16th century. This phenomenon constituted the renaissance of remedial journey, which was popular already in antiquity. Spa travel of polish bishop Józef Stanisław Sapieha and his fellows of journey makes a curious example of abroad trips in Poland in this time. Very important historic source is little known account from this voyage which author was Lithuanian treasure writer Ignacy Łopaciński. This account of travel gives imagination about course of travel and it priorities. This reading shows that the treatment was not sole purpose of departure. It results from fact that descriptions of cure were relatively short. Sickness troubles, which made difficult daily life and social functioning representatives of polish gentry and aristocracy, were not in condition to exclude touristic aim of journeys. Polish spa travels in 17 and 18th centuries, especially expedition of bishop Sapieha, it’s possible to recognize early sign of European cultural tourism, which consist in intensive sightseeing following places, cities and architectural objects.